Magnetic susceptibility record of the Pod Barrandovem section (Praha Formation) - Anne-Christine Da Silva; Jindra Hladil; Mark J Dekkers; Leona Chadimova; Ladislav Slavik (PANGAEA, 2024)
The Early Devonian geological time scale (base of the Devonian at 418.8 ±2.9Myr, Becker et al. (2012; doi:10.1016/B978-0-444-59425-9.00022-6) suffers from poor age control, with associated large uncertainties between 2.5 and 4.2 Myr on the stage boundaries. Identifying orbital cycles from sedimentary successions can serve as a very powerful chronometer to test and, where appropriate, improve age models. Here, we focus on the Lochkovian and Pragian, the two lowermost Devonian stages. High-resolution magnetic susceptibility (χin- 5 to 10 cm sampling interval) record are gathered from one main limestone section, the Pod Barrandovem (174 m; Praha Formation) in the Czech Republic. This record is used with two other records (Pozare and Branzovy) to provide a cyclostratigraphic time scale and to provide time estimates for the Lochkovian and Pragian. Magnetic susceptibility (χin) measurements have been carried out in different laboratories. Using a KLY-2 at the Czech Academy of Sciences and a MFK-1 at Utrecht University, both are Kappabridge device, manufactured by AGICO (Brno, Czech Republic).